Role of Denver II and Development Quotients in the management of several pediatric developmental and behavioral disorders - Titi Sularyo; Bernie Endyarni; Tri Lestari H; Tirza Z. Tamin; Gitayanti Gitayanti (Indonesian Pediatric Society, 2012)
Background Autism spectrum disorder (ASD) and attention deficitand hyperactivity disorder (ADHD) are nowadays becoming moreand more frequently found. Parents are worried of the possibilitythat their children suffer from them. Growth and developmentclinics (GDC) should be able to deliver professional services. Thusa practica applicable, objective, valid, reliable, and able to measuredevelopment quotient (DQ) values instrument is needed.Objective To find out whether the Denver II instrument andDQ values can be used in the management of children with ASDandADHD.Methods A study was carried out on cases of children withASD, multisystem development disorder (MSDD), pervasivedevelopment disorder - n ot otherwise specified (PDD-NOS), andattention deficit and hyperactivity disorder (ADHD), consistingof history taking, physical examination, establishing diagnosis,therapy, evaluation, and follow-up. The Denver II instrumentwas used and DQ values in all development streams established.The study was done at the GDC of Hermina Depok Hospital inJuly 2008 - June 2009.Results It revealed that results of the Denver II as seen on thefilled Denver II form showed